Safety and pharmacokinetics of escalating doses of neutralising monoclonal antibody CAP256V2LS administered with and without VRC07-523LS in HIV-negative women in South Africa (CAPRISA 012B): a phase 1, dose-escalation, randomised controlled trial. Issue 4 (April 2023) - Mahomed, Sharana; Garrett, Nigel; Capparelli, Edmund V; Osman, Farzana; Mkhize, Nonhlanhla N; Harkoo, Ishana; Gengiah, Tanuja N; Mansoor, Leila E; Baxter, Cheryl; Archary, Derseree; Yende-Zuma, Nonhlanhla; Samsunder, Natasha; et al.
Summary: Background: Young women in sub-Saharan Africa continue to bear a high burden of HIV infection. Combination anti-HIV monoclonal antibodies are a potential HIV prevention technology that could overcome adherence challenges of daily oral pre-exposure prophylaxis. In this phase 1 clinical trial we aimed to determine the safety and pharmacokinetic profile of the broadly neutralising monoclonal antibody CAP256V2LS. Methods: CAPRISA 012B, a first-in-human dose-escalation phase 1 trial evaluated the safety, pharmacokinetics, and neutralisation activity of CAP256V2LS alone and in combination with VRC07-523LS in young HIV-negative women in Durban, South Africa. Groups 1 and 2 were open label with CAP256V2LS administered at 5 mg/kg and 10 mg/kg intravenously and 5 mg/kg, 10 mg/kg, and 20 mg/kg subcutaneously. In group 3, participants were randomly allocated to receive a combination of CAP256V2LS and VRC07-523LS at 10 mg/kg and 20 mg/kg subcutaneously comixed with ENHANZE, a recombinant human hyaluronidase. Once safety was established in the first three participants, dose escalation took place sequentially following review of safety data. Primary endpoints were the proportion of participants with mild, moderate, and severe reactogenicity or adverse events, graded as per the Division of AIDS toxicity grading. The trial is registered on the Pan African Clinical Trial Registry, PACTR202003767867253, and is recruiting. Findings: From July 13, 2020, to Jan 13, 2021, 42 HIV-negative women, aged 18–45 years, were enrolled. All 42 participants, eight with intravenous and 34 with subcutaneous administration, completed the trial. There were no serious adverse events or dose-limiting toxicities. Most commonly reported symptoms following intravenous administration were headaches in seven (88%) and nausea in four (50%) participants. Commonly reported symptoms following subcutaneous administration were headache in 31 (91%), chills in 25 (74%), and malaise or fatigue in 19 (56%) participants. Adverse events included transient lymphocytopenia in eight (19%), proteinuria in nine (21%), elevated aspartate aminotransferase in ten (24%), and alanine aminotransferase in five (12%) participants. Interpretation: CAP256V2LS administered alone and in combination with VRC07-523LS was safe with favourable pharmacokinetics and neutralisation activity, supporting further assessment in larger clinical studies. Funding: European and Developing Countries Clinical Trials Partnership, South African Medical Research Council, and South African Department of Science and Innovation.